1980
DOI: 10.1136/gut.21.7.607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nissen fundoplication on competence of the gastro-oesophageal junction.

Abstract: SUMMARYThe changes produced by the Nissen fundoplication were measured in 12 patients, who required surgery to control their reflux oesophagitis. The gastro-oesophageal junction of each patient was studied before and three months after operation by station pullthrough manometry and prolonged pH monitoring of the distal oesophagus. All patients were free from reflux symptoms post-operatively. The Nissen fundoplication resulted in a significant increase in the pressure, but not the length, of the lower oesophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 17 publications
4
4
0
1
Order By: Relevance
“…12 Furthermore, in a small series of patients studied previously using video manometry, we also found a weak correlation between dysphagia for solid food and lower esophageal sphincter residual relaxation pressure (r=0.37, p=0.04). 13 Previous studies have also shown that laparoscopic Nissen fundoplication is followed by an increase in lower esophageal sphincter resting and residual relaxation pressures, 14,15 and the results of our current study are consistent with these findings. Other studies, including randomized trials, have shown that the increase in lower esophageal sphincter resting pressure is less after various anterior partial fundoplication procedures, and this is associated with a lower incidence of dysphagia.…”
Section: Discussionsupporting
confidence: 95%
“…12 Furthermore, in a small series of patients studied previously using video manometry, we also found a weak correlation between dysphagia for solid food and lower esophageal sphincter residual relaxation pressure (r=0.37, p=0.04). 13 Previous studies have also shown that laparoscopic Nissen fundoplication is followed by an increase in lower esophageal sphincter resting and residual relaxation pressures, 14,15 and the results of our current study are consistent with these findings. Other studies, including randomized trials, have shown that the increase in lower esophageal sphincter resting pressure is less after various anterior partial fundoplication procedures, and this is associated with a lower incidence of dysphagia.…”
Section: Discussionsupporting
confidence: 95%
“…Although SART is a less sensitive and specific method for measuring reflux, than 24-hour pH monitoring [24], the former pH-metric assessment was effective enough to provide good corre lation in most cases. As in other series [4,6,[8][9][10]23] manometric data confirm that Nissen fundoplication results in a significant increase of the average LES pres sure up to normal values. However, in some patients LES pressure remains below the normal value without any effect on the clinical result [10,23].…”
Section: Effectiveness O F the Nissen Fundoplicationsupporting
confidence: 72%
“…As in other series [4,6,[8][9][10]23] manometric data confirm that Nissen fundoplication results in a significant increase of the average LES pres sure up to normal values. However, in some patients LES pressure remains below the normal value without any effect on the clinical result [10,23]. Such data rein force the concept that LES is not necessarily the most important factor in preventing reflux [8,24], Long-term effectiveness of the procedure is more con troversial.…”
Section: Effectiveness O F the Nissen Fundoplicationsupporting
confidence: 72%
“…The disappearance of projectile vomiting following pyloromyotomy seems to be related to the improvement oflower oesophageal function as weB as better passage through the postoperative pylorus. Some authors (5)(6)(7)(8) have investigated the barrier to refl ux of gastric contents at the gastroesophageal junction by oesophageal manometry. In the present study we used oesophageal manometry to examine the lower oesophageal function before and after pyloromyotomy.…”
Section: Discussionmentioning
confidence: 99%